PERAN AYAH SEBAGAI BREASTFEEDING FATHER DALAM PEMBERIAN ASI EKSKLUSIF PADA BAYI: A LITERATURE REVIEW - Nabila, Nabila Amelia Hanisyah Putri; Agus Isnaen; Hesteria Friska Armynia Subratha; Nis’atul Khoiroh (JURNAL SIPAKALEBBI, 2023)
WHO recommendations for babies aged 0-6 months are breastfeeding as the best food and drink for babies, which is called exclusive breastfeeding. ASI has a complete nutritional content, to increase the child’s immune system, children’s intelligence and children’s motor skills. This will increase body immunity also tends to prevent children from allergies and diarrhea due to the hygiene of breast milk. In addition, ASI also has the right nutritional components for the growth and development of children. However, globally, exclusive breastfeeding for infants aged <6 months is reported to be less than 40%, so various efforts are needed to increase the success of exclusive breastfeeding. There are various factors that determine the success of breastfeeding, namely cultural support, knowledge of mothers and health workers to husband’s support which are very influential in the success of exclusive breastfeeding. Husband’s support is a very important factor because the husband or father of the baby is the closest person who can encourage the mother to continue to provide exclusive breastfeeding. The purpose of this study was to find out the findings regarding the importance of the father’s role as a breastfeeding father in supporting the success of exclusive breastfeeding. This study used a descriptive research design with a literature review approach, and uses several article databases. The results of this study used 9 articles that examined the role of father breastfeeding in efforts to support the success of exclusive breastfeeding. The conclusion of this study is that the role of breastfeeding fathers is very important in achieving the success of exclusive breastfeeding. The existence of emotional support, a role in the smooth production of breast milk, to the knowledge and involvement of the father and the division of roles are factors that support the success of exclusive breastfeeding.